Determinants of Financial Distress in Property and Real Estate Companies - Inggriyani Wilda Utami; Titis Puspitanigrum Dewi Kartika (STIE Perbanas Surabaya, 2019)
This study aims to examine the effect of financial ratios, consisting of operating capacity, quick ratio, working capital, and cash flow to sales, on financial distress. Financial distress is an interesting topic to discuss because research on this factor can predict the company’s survival. In general, financial distress can be measured by analyzing financial statements. Financial statements are very useful for the companies to find out their financial position as the results of their operations in a given period. This study used the population concerning property and real estate companies listed on the Indonesia Stock Exchange in the period 2015-2017. This study used a purposive sampling technique for getting the sample. The population consists of 99 companies that meet the criteria as stipulated for the sample selection. The analytical method used is logistic regression with a significance level of 0.05. The test results in this study indicate that operating capacity has an effect on financial distress, while quick ratio, working capital and cash flow to sales have no effect on financial distress.